Forecasting the career growth potential of university graduates - K. B. Gerasimov; N. Yu. Prosvirkin (Вестник университета, 2022)
This article aims to determine which employability skills best predict career potential. The regression analysis method was used to process the results of a survey of HR managers and it allowed to identify the employability skills that show the highest relationship with promotion. The results of the regression formed models of structural equations. The authors note that job-required leadership skills and information technology skills contribute significantly to the career growth potential of recent graduates. In addition, the authors found that the managerial skills, leadership qualities, and basic literacy skills identified in recent graduates by their employers are the strongest determinants of graduate career potential. The practical implications of the study show that it is important for trainees to develop basic employment skills prior to entering a job, as remedial on-the-job training can hinder career progression.